2019
DOI: 10.1080/13696998.2019.1615927
|View full text |Cite
|
Sign up to set email alerts
|

Treatment discontinuation of long-acting injectables or oral atypical antipsychotics among Medicaid recipients with schizophrenia

Abstract: Aims: Among patients with schizophrenia, poor adherence and persistence with oral atypical antipsychotics (OAA) often results in relapse and hospitalization. Second-generation antipsychotic long-acting injectables (SGA LAI) have demonstrated higher adherence than first-generation antipsychotic LAI and OAA therapies. This study aimed to determine whether SGA LAIs are associated with better persistency compared to OAA among Medicaid recipients with schizophrenia. ), patients aged 18 years with schizophrenia and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
3
10
0
Order By: Relevance
“…In this claims data study, we found that patients who initiated AOM were, indeed, less likely to discontinue treatment compared with those who initiated OA in routine clinical practice in Japan (adjusted HR 0.54, 95% CI 0.43-0.68). Our findings are consistent with trends observed in other claims data studies showing that AOM users in the USA are less likely to discontinue treatment (HR 0.69, 95% CI 0.60-0.79) [15] and have significantly longer time to discontinuation than oral antipsychotic users [16]. Although our results showed the advantage of AOM in treatment continuation, there were some biases to be considered when interpreting the results of this study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this claims data study, we found that patients who initiated AOM were, indeed, less likely to discontinue treatment compared with those who initiated OA in routine clinical practice in Japan (adjusted HR 0.54, 95% CI 0.43-0.68). Our findings are consistent with trends observed in other claims data studies showing that AOM users in the USA are less likely to discontinue treatment (HR 0.69, 95% CI 0.60-0.79) [15] and have significantly longer time to discontinuation than oral antipsychotic users [16]. Although our results showed the advantage of AOM in treatment continuation, there were some biases to be considered when interpreting the results of this study.…”
Section: Discussionsupporting
confidence: 92%
“…This also paralleled the trend of better adherence with risperidone LAI compared with orally administered risperidone [12]. Our results would also add to the benefits of LAIs compared with oral antipsychotics in terms of a longer treatment duration, previously reported for paliperidone, risperidone, and haloperidol [7,14,15]. Now that the advantages of LAIs over oral antipsychotics in treatment persistence seem to be evident, the next research topic may be a comparison among LAIs.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Even if there are studies show that treatment interruptions with oral medications are by far one of the main causes of schizophrenia relapse and rehospitalization, [ 21 ] the use of LAIs should be considered in optimize adherence, improve treatment outcomes, and enhance functioning by reducing the frequency of administration, [ 22 , 23 ] the prescribing rate of long-acting injectable formulations of risperidone and paliperidone in this study isvery low. The barriers to LAIs use may be insufficient psychiatrists’ clinical understanding of the use of LAIs, the lack of patient insight into the disease and the treatment, and the limitations on healthcare policy.…”
Section: Discussionmentioning
confidence: 97%